SPLINTING PERIODONTAL ESTETIK DENGAN FIBER KOMPOSIT TINJAUAN PUSTAKA - Tetty Waty R Sianturi; Rini Octavia Nasution (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2021)
Introduction: Tooth mobility is the most often experienced by people with a periodontal disease where one of the treatments that can be done to stabilize teeth with mobility is by splinting fibers composite. This literature review will explain the use of fiber composite splints in the tooth with mobility due to periodontal disease. Review: Splinting is a treatment for teeth with mobility that vary in options. Removable or permanent splints can be made of composite materials, acrylic, wire, or a combination of composite materials with fiber. The various form of splinting treatments has their advantages and disadvantages. Splinting with fiber composites is carried out using 2 techniques, namely extra coronal and intracoronary depending on the patient's dental condition. The extra coronal splinting technique is usually performed by placing the composite fiber directly without tooth preparation. The intra-coronal splinting technique requires horizontal preparations that are interconnected with a width of 2-3 mm and a depth of 1-2 mm. In anterior teeth, preparation is usually done in the middle to one-third of the incisal area of the tooth, whereas in posterior teeth it is usually done on the occlusal surface. Splinting with fiber composites has been developed in the field of dentistry which aims to improve tooth stability because it has almost the same strength as metal, is non-corrosive, easy to apply, smooth surface that is translucent, and radiolucent, and has good aesthetic properties. Conclusion: The use of fiber composite splinting is the best choice in terms of advantages and aesthetic factors, as well as accelerating tissue healing response.